Motion Tracking in TAG. - Bowcott, Peter; Brow Trash, Low (Performance Research, 2006)
The article discusses the software structure, components, and technology of the digital interactive game of TAG. The game utilizes motion tracking technology to provide gamers with unique experiences in terms of determining who is in charge of the game and who is playing or who is being played during the game. Moreover, the article discusses the program and functionality of the game as well as the x, y mapping coordinates that is projected in the game.